Impacts of COVID-19 on construction: Case study of IJM construction project / Lee Chun Yee - Lee , Chun Yee (2021)
The impacts of coronavirus (COVID-19) on the time and cost of building projects are investigated and computed in this study, with a focus on three construction dimensions: suspension of Site, supply chain and construction worker productivity. Three techniques were used to obtain conclusions on the topic: one case study and the use of Primavera 6 software to evaluate schedule delay for all the delay events. The case study is based on a real-life building project that was underway while the pandemic was at its most severe (March 2020). Interviews with project managers, minutes from progress meetings and interim progress certificates are also included in the data. COVID-19 has hampered construction progress in two ways: 1) delays resulting from the closure of site during MCO; and 2) labour disruptions resulting from restrictions on gatherings, as well as stringent SOPs required like social distancing, taking of temperature, mandatory COVID-19 test, frequent sanitisation and etc. The findings imply that contractors should request compensable time extensions because they provide the foundation for a credible claim that will result in additional time and additional cost. Future research might look at integrating tools and procedures into the bidding and building process to reduce the impact of such future scenarios caused by a pandemic or other force majeure event.